Pengaruh Arus Kas Operasi, Arus Kas Investasi, Arus Kas Pendanaan,Terhadap Roi Pada Pt Astra Inernasional (Persero) Tbk Tahun 2016-2021 - Tri Widiastuti; Fazhar Sumantri; Rahmania Apriliani; Cahya Eni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Researchers will discuss cash flow management, cash flow financing, and the impact of investment cash flow on the ROI of PT ASTRA INTERNASIONAL. Financial statement cash flows are very important to know the inflows and outflows of a company's funds. Prastowo and Juliaty (2005: 149) stated that cash flow is the lifeline of any business. This study was conducted because investigators wanted to know how much cash flow would affect a company's ROI. In this study, researchers use a quantitative descriptive research method by collecting existing data, examine the results of the data with survey variables, analyze the results of the data variables, and see how much cash flow they have. Investigate whether it affects. ROI of the company of PT Astra International.